HOW SOCIAL ARE ISLAMIC BANKS IN PAKISTAN? - Irfan, Rafea (International Journal of Islamic Business & Management, 2021)
Purpose: This research paper attempts to prove that social outcomes are one of the objectives of Islamic banks and tries to investigate whether social failure exists in the Islamic banking sector of Pakistan by assessing the social performance of Islamic banks against performance indicators of social outcomes. Design/ Methodology/ Approach: In this paper content analysis of annual reports of a sample of 4 Islamic conventional banks and 4 Islamic banking units functioning in Pakistan is conducted. The social outcomes that are attempted to be measured of the Islamic banks in this research paper are derived from social objectives present in literature, in addition to this, Kinder, Lydenberg, Domini Research, 17 Sustainable Development goals of the United Nations, five Environment Social Governance scorecards developed by Oikocredit which is a global cooperative and social investor group, and Analytics index of corporate social performance are used for the derivation of social outcomes. Findings: Conventional Islamic banks in Pakistan are doing better than Islamic banking units on measures of social responsiveness. Originality/ Value: This research paper is based on the framework of the research paper “How social is Islamic banking” written on the Islamic banking sector of Indonesia by Luthfi Hamidi and Andrew C. Worthington. JEL Classification Codes: G0, G2, P4, Q3.